Edukasi Fiqih Makanan Halal-Haram Bagi Remaja Masjid Al-Hidayah Desa Kujangsari Kota Banjar - Hanipudin, Sarno; Taqiyudin Subki; Sri Mulyani; Kartika Wanojaleni (LP3M IAIFA Kediri, 2023)
Today, various foods are easily found in roadside stalls and even supermarkets. However, one thing that must be considered is the halal status of these foods. Halal food awareness should be taken seriously, as it is related to Islamic doctrine. Educational efforts are important, and as a protective measure for the development of Muslim youth, it is crucial. The target group for this guidance is the Youth of Al-Hidayah Mosque, who are a community of youth actively participating in religious activities held at the mosque. However, there has been no specific guidance regarding halal and haram foods for them. This guidance aims to provide education to the Youth of Al-Hidayah Mosque about the understanding of permissible (Halal) and prohibited (Haram) foods. The target participants for this activity are 30 Youth of Al-Hidayah Mosque.